2017
DOI: 10.1186/s12864-017-3509-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct histone methylation and transcription profiles are established during the development of cellular quiescence in yeast

Abstract: BackgroundQuiescent cells have a low level of gene activity compared to growing cells. Using a yeast model for cellular quiescence, we defined the genome-wide profiles of three species of histone methylation associated with active transcription between growing and quiescent cells, and correlated these profiles with the presence of RNA polymerase II and transcripts.ResultsQuiescent cells retained histone methylations normally associated with transcriptionally active chromatin and had many transcripts in common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 55 publications
2
61
0
Order By: Relevance
“…Transcriptome analysis of quiescence exit in shake flask cultures showed an immediate upregulation of at least 2500 genes within 360 s (Radonjic et al 2005). Distinct histone methylation and transcription profiles were observed for quiescence in yeast, which can rapidly be reversed and resume growth (Young et al 2017). Laporte et al found that the metabolic status and flux rather than cell cycle regulators are the principal triggers for the quiescence exit.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis of quiescence exit in shake flask cultures showed an immediate upregulation of at least 2500 genes within 360 s (Radonjic et al 2005). Distinct histone methylation and transcription profiles were observed for quiescence in yeast, which can rapidly be reversed and resume growth (Young et al 2017). Laporte et al found that the metabolic status and flux rather than cell cycle regulators are the principal triggers for the quiescence exit.…”
Section: Introductionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae , quiescence is typically induced by nutrient limitation, but it is not a starvation state. Faced with a waning nutrient supply, these cells down-regulate highly conserved signaling pathways that promote proliferation and redirect their gene expression and metabolism to stockpile nutrients and induce processes that promote long-term survival (Lillie and Pringle, 1980; Sillje et al ., 1999; Francois and Parrou, 2001; De Virgilio, 2012; McKnight et al ., 2015; Young et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The other cells in the population are non‐quiescent (NQ) and may continue proliferating. The organization of a Q cell's internal structures and genome is very different from that of a NQ cell – there is an increase in the storage carbohydrates and stress protectants glycogen and trehalose, an increased width of the cell wall (Aragon et al ., ), sequestration of proteins (Suresh et al ., ), telomere clustering (Guidi et al ., ; Laporte et al ., ; Rutledge et al ., ) and transcriptional shut down (McKnight et al ., ; Young et al ., ). The most significant evolutionary property of yeast quiescent cells is their ability to maintain viability over long periods of time during the growth‐arrested phase and to resume mitotic growth once growth‐promoting conditions are restored (Gray et al ., ).…”
Section: Example III Quiescencementioning
confidence: 97%